EVALUASI PERKEMBANGAN WISATA BAHARI DI PANTAI SANUR - Gautama, IGA Gede Oka; Sunarta, I Nyoman (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012, 2012)
Growth of coastaltourism Sanur automatically will change physical characteristic and social of the area, because a developed area is inevitable from the cycle of change that constantly evolves. Empirical experience as well as issues about Sanur’s coast, such as: the change of tourist motivation, environmental pollution and social problems considers an evaluation to assess the developments. The main purpose of this research is, to solve the problems occurred by evaluating ways to find out: (1) factor that attract tourist to conduct maritime tourism in Sanur costal area (2) how the  characteristics of Sanur’s in supporting coastal tourism activity (3) step to creating sustainable tourism in Sanur. This research used a qualitative descriptive analysis approach, in this study the data were collected in the original condition. Researcher as the primary means of collecting data, by Observation, spread questionnaire, deep interview method and the sample taken by purposive sampling. Literature and the result of research will analysis by descriptive qualitative, start transforming raw data into a easily understandable data including preparing, manipulate and present the data become an information. Then the data interpretation as the principal study. Result in this reseach are: factor that  attract tourists to conduct coastal tourism is, the hospitality with result found 90% tourists argues both. Characteristics of coastal Sanur areasuitable for all types of water sport, fun dive and water recreation activities. step to creating sustainable tourism in Sanur are with the integrated coastal zone management approach, like integration between: sectoral, science, and ecological. After that can be combined with the concept of zoning. Suggestion to create sustainable coastal tourism in Sanur are (1) coherence between sectoral and academics integration, need to update the rules and regulations concerning coastal tourism (2) having a detailed plan of utilization of spatial or zoning of coastal (3) attention for the carrying capacity (4) build facilities that can save the coastal environment.
Keywords: Evaluated development, coastal tourism, sustainable tourism